2021
DOI: 10.1039/d0cp05990k
|View full text |Cite
|
Sign up to set email alerts
|

Soft X-ray emission spectroscopy for the electronic state of water molecules influenced by plasma-treated multi-walled carbon nanotubes

Abstract: In this study, soft X-ray emission spectroscopy of an aqueous colloidal dispersion of multi-wall carbon nanotubes modified via plasma process in an aqueous solution was performed for investigating the electronic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…The C 3 N 4 nanosheets were synthesized by heating urea at 823 K for 2 h in air. 29 The plasma surface modification of C 3 N 4 was performed under previously reported plasma conditions: 52 nonequilibrium plasma was generated in 100 mL of 0.1 g L −1 NaCl aqueous solution containing 4 wt % hydroquinone, by applying 1.2 kV of bipolar pulsed voltage at 80 kHz to tungsten rod electrodes (1 mm in diameter) placed with 2 mm gap. The current−voltage (I−V) characteristics and a photograph of the plasma are shown in Figure S1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The C 3 N 4 nanosheets were synthesized by heating urea at 823 K for 2 h in air. 29 The plasma surface modification of C 3 N 4 was performed under previously reported plasma conditions: 52 nonequilibrium plasma was generated in 100 mL of 0.1 g L −1 NaCl aqueous solution containing 4 wt % hydroquinone, by applying 1.2 kV of bipolar pulsed voltage at 80 kHz to tungsten rod electrodes (1 mm in diameter) placed with 2 mm gap. The current−voltage (I−V) characteristics and a photograph of the plasma are shown in Figure S1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In previous reports on the plasma surface modification of C 3 N 4 , plasmas were generated in the gas phase (typically Ar gas was used), with O 2 , N 2 , or NH 3 used as feeding gases to introduce oxygen-or nitrogen-containing functional groups and/or surface defect sites on C 3 N 4 , 46−50 such as photocatalytic H 2 production at the plasma-modified sites on C 3 N 4 . By contrast, our group recently reported the plasma surface modification of hexagonal boron nitride nanosheets 51 and multiwalled carbon nanotubes 52 using plasma generated in an aqueous solution containing hydroquinone as a precursor for oxidative surface modification. It was reported that in this plasma surface modification, polymerization of the added hydroquinone enabled carbon layer deposition on the particles.…”
Section: ■ Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Carbon layer formation on hBN particles was demonstrated using plasma in hydroquinone aqueous solution, and the carbon layer formed on hBN was characterized. Hydroquinone was expected to act as a precursor of the carbon layer and radical donator to assist the oxidization process during plasma processing. , The modified hBN particles were analyzed by Raman spectroscopy to confirm the formation of a carbon layer on the surface and electron spin resonance (ESR) spectroscopy to detect dangling bonds. The reactivity of the carbon layer formed on hBN was confirmed by further functionalization with isocyanate groups.…”
Section: Introductionmentioning
confidence: 99%
“…Hexagonal boron nitride (hBN), which has a graphite-like structure, has attracted attention due to its superior thermal conductivity and electrical insulating properties. In recent years, as a two-dimensional layered material, hBN has shown great potential in many applications in substrates for graphene electronics, optical devices, , and composite materials. In particular, polymer composites with hBN particles as thermally conductive and electrically insulating fillers are expected to act as thermal management materials to address heat accumulation in electronic devices with higher integration. For such applications, the surface modification of hBN particles is essential to improve dispersibility in polymer matrices and form strong filler–polymer bonds, thus realizing organic/inorganic composites that combine the mechanical properties of polymer matrices with thermal conductivity at high filler contents. Among surface modification techniques using dispersants , and oxidization, , plasma processing is an effective method for hBN surface modification because the highly energetic species in plasma can break stable B–N bonds and enable the in-plane functionalization of hBN. , Plasma in solution is particularly suitable for the surface modification of inorganic particles because stirring solution during the process can suppress particle agglomeration and promote effective reactions between particles and high-density excited species. ,, However, even with plasma processing, it is difficult to make reactive hBN surfaces allowing designable functionalization because of the scarcity of reactive sites such as dangling bonds …”
Section: Introductionmentioning
confidence: 99%